AB1045 Efficacy of Etanercept on Radiographic Progression in Adult Patients with Rheumatoid Arthritis or Psoriatic Arthritis: Results from The Second Interim Analysis of A German Non-Interventional, Prospective, Multi-Center Study. (15th July 2016) - Wassenberg, S.; Rau, R.; Klopsch, T.; Buecheler, M.; Meng, T.; Loeschmann, P.-A.
Abstract : Background: Several clinical trials have shown that etanercept (ETN) is highly effective in reducing clinical disease activity and reaching remission while it may also decrease and even reverse radiographic progression in rheumatoid arthritis (RA) and in psoriatic arthritis (PsA). However, the proportion of patients with RA or PsA achieving remission and radiographic non-progression in routine everyday practice is not known. Objectives: To assess radiographic change and clinical disease activity in RA and PsA patients during long-term routine use of ETN under real-world conditions in a non-interventional trial. This is an interim analysis of the data after 52–78 weeks of observation per patient. Methods: 1, 600 adult RA and 400 PsA patients will be included into the study. Radiographs of hands and feet taken at baseline (±3 months start of ETN treatment), after 12 to 18 and 36 months follow up and 12 to 36 months before baseline ("historic"), if available, are scored by 2 blinded readers with random time order by the "van der Heijde modified Sharp score" 1 (mTSS RA ) for RA patients and the "van der Heijde modified Sharp score adapted" 2 (mTSS PsA ) for PsA patients. Additional parameters such as disease activity score (DAS28) and (serious) adverse events are recorded regularly. Results: 282 RA and 87 PsA patients (77% vs. 51% females) were evaluated for this interim analysis. The median disease duration at baseline was 5.3 (range: 0;46) years (RA) and 4.3 (0;37) years (PsA). At baseline, mean mTSS RA was 22.1±33.2 (n=136), mean mTSS PsA was 21.6±30.6 (n=34). X-rays after 52–78 weeks were available for 131 RA (32 PsA) patients with a mean annualized radiographic progression of 1.4±6.4 (-0.9±4.2) under ETN therapy. During ETN treatment, 29.8% RA (28.1% PsA) patients experienced no change (-0.5 to 0.5) and 30.5% RA (43.8% PsA) an improvement (<-0.5) in mTSS. In total, numerically more PsA than RA patients were considered to be in radiographic non-progression (60.3% RA vs. 71.9% PsA, change in mTSS RA/PsA ≤0.5 from baseline). 65 RA (16 PsA) patients had a historic (i.e. 12–48 months prior to baseline) and a baseline x-ray with a mean annualized radiographic progression of 3.7±21.3 (2.1±3.5). Comparison between the annualized radiographic progression under ETN therapy with prior disease progression (before baseline x-ray) revealed less annual radiographic progression under therapy with ETN in both treated groups (RA: n=61; -3.6±22.1; p=0.205, PsA: n=14; -3.5±6.1; p=0.049). In RA (PsA) patients, the DAS28 decreased from a mean baseline value of 4.6±1.3 (4.2±1.0) to 2.9±1.2 (2.4±1.0) at week 78 indicating an important decrease of disease activity under ETN treatment. At week 78 fewer RA than PsA patients reached remission (DAS28<2.6) (44.6% RA vs. 60.7% PsA). Treatment with ETN was well tolerated and no new safety signals were observed. Conclusions: The results of this interim analysis suggest that treatment with ETN slows radiographic progression and reduces disease activity in RA and PsA patients in routine clinical care. References: J Rheumatol 2000; 27: 261–63; Ann Rheum Dis 2005; 64: (Suppl II):ii61-ii64 Acknowledgement: The study was sponsored by Pfizer Pharma GmbH Disclosure of Interest: S. Wassenberg Consultant for: Chugai, Janssen, Novartis, Pfizer, Speakers bureau: Abbvie, Chugai, Janssen, MSD, Pfizer, Roche, R. Rau: None declared, T. Klopsch Shareholder of: Abbvie, Amgen, Gilead, Novartis, Roche, Consultant for: Abbvie, BMS, Pfizer, Roche, UCB, M. Buecheler Employee of: Pfizer Pharma GmbH, T. Meng Employee of: Pfizer Pharma GmbH, P.-A. Loeschmann Employee of: Pfizer Pharma GmbH